2008
DOI: 10.1074/jbc.m804464200
|View full text |Cite
|
Sign up to set email alerts
|

The Sushi Domains of Secreted GABAB1 Isoforms Selectively Impair GABAB Heteroreceptor Function

Abstract: GABA B receptors are the G-protein-coupled receptors for ␥-aminobutyric acid (GABA), the main inhibitory neurotransmitter in the brain. GABA B receptors are promising drug targets for a wide spectrum of psychiatric and neurological disorders. Receptor subtypes exhibit no pharmacological differences and are based on the subunit isoforms GABA B1a and GABA B1b . GABA B1a differs from GABA B1b in its ectodomain by the presence of a pair of conserved protein binding motifs, the sushi domains (SDs). Previous work sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 38 publications
1
46
0
Order By: Relevance
“…Specifically, we addressed whether functional GABA B heteroreceptors are present in cultured pyramidal neurons of 1b Ϫ/ Ϫ mice, but absent in neurons of 1a Ϫ/ Ϫ mice. Activation of GABA B heteroreceptors by baclofen, a GABA B receptor agonist, inhibits the spontaneous release of glutamate and as a result reduces the miniature EPSC (mEPSC) frequency (Yamada et al, 1999;Tiao et al, 2008). We found that baclofen strongly reduced the mEPSC frequencies in wild-type (WT) and 1b Ϫ/ Ϫ neurons, while baclofen only marginally reduced the mEPSC frequency in 1a Ϫ/ Ϫ neurons ( Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Specifically, we addressed whether functional GABA B heteroreceptors are present in cultured pyramidal neurons of 1b Ϫ/ Ϫ mice, but absent in neurons of 1a Ϫ/ Ϫ mice. Activation of GABA B heteroreceptors by baclofen, a GABA B receptor agonist, inhibits the spontaneous release of glutamate and as a result reduces the miniature EPSC (mEPSC) frequency (Yamada et al, 1999;Tiao et al, 2008). We found that baclofen strongly reduced the mEPSC frequencies in wild-type (WT) and 1b Ϫ/ Ϫ neurons, while baclofen only marginally reduced the mEPSC frequency in 1a Ϫ/ Ϫ neurons ( Fig.…”
Section: Resultsmentioning
confidence: 78%
“…The tertiary structure of SDs is fixed by two intramolecular disulfide bridges that are critical for interaction with other proteins (Soares and Barlow, 2005). Consistent with their role as interaction motifs, the SDs of GABA B1a recognize binding sites in neuronal membranes (Tiao et al, 2008).…”
Section: Introductionmentioning
confidence: 83%
“…SD1 interacts with the extracellular matrix protein fibulin-2 in vitro (23), and there is evidence that CCAAT/enhancer-binding protein homologous protein (CHOP) differentially interacts with R1a (31). In addition, a soluble excreted isoform of part of R1a, defined as R1j, is mostly composed from the two SDs (32,33), and this inhibits the function of GABA B heteroreceptors and recognizes binding partners on neuronal membranes. However, the sites of attachment have not been identified (33).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a soluble excreted isoform of part of R1a, defined as R1j, is mostly composed from the two SDs (32,33), and this inhibits the function of GABA B heteroreceptors and recognizes binding partners on neuronal membranes. However, the sites of attachment have not been identified (33). It is, therefore, likely that the SDs interact with other proteins that could modulate the signaling and trafficking of GABA B R1aR2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Because the sushi repeats are the only difference between GABA B1a and GABA B1b , it is to be expected that proteins interacting with these domains target or retain the GABA B1a isoform to specific microdomains. Consistently, a soluble recombinant protein of the two sushi repeats binds to neuronal membranes with low nanomolar affinity (10). An interaction of one of the two sushi repeats with fibulin-2 has been described (11), but the functional implication remains elusive.…”
mentioning
confidence: 99%